Orexigen : valuing contrave - Calkins, Tim (London : Kellogg School of Management, 2016)
In January 2013, small biotechnology firm Orexigen was in the final stages of testing Contrave, a promising new pharmaceutical product for the treatment of obesity. At the time, Orexigen had no products in the market, so all its hopes of financial success rested on this new treatment. Contrave had proven to be highly effective in clinical trials, and Orexigen executives were confident it would receive FDA approval.At the same time, a much larger pharmaceutical company was considering acquiring Orexigen. Because the decision to acquire would ultimately be a financial one, the project team from the large company had to complete a valuation for Orexigen's only significant product in its pipeline, Contrave. What was the new product actually worth?
Originally published in Calkins, T. (2016). Orexigen: Valuing Contrave. 5-113-001. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Consolidation and merger of corporations -- Case studies; Pharmaceutical biotechnology -- Case studies